Rancang Bangun Human Resource Information System Berbasis Web - M Aldi Nugraha; Yosep Septiana; Dini Destiani Siti Fatimah (Jurnal Algoritma, 2022)
Clinics have human resources that aim to support the needs of health services to provide health services to patients. At the Medika Cempaka Garut Clinic, employee data management is ongoing using recording and archiving for each employee data and has not been computerized, using the archiving method in book form and written on paper data may be lost and carrying out data search activities takes a long time. takes a long time, and health services are felt to be lacking because of unskilled human resources and a lack of service to the wishes of patients, which can reduce trust and reduce the image of the clinic in the eyes of the public. Based on these problems the Human Resource Information System (HRIS) is a solution that can be applied to manage human resource information systems. So from these problems a system was created that could manage human resources for clinics, with the Human Resource Information System able to make an optimal contribution in terms of managing human resource data. In compiling this research for data collection conducting observations, interviews, and the Human Resource Information System information system using the Rational Unified Process method, this method has an empathic phase, namely inception, elaboration, construction and transition, where modeling is using the Unified Modeling Language, while for making applications using the PHP language along with the Yii2 framework and for the database using MySql. In the end, this research resulted in a Human Resource Information System application that can be accessed via a web browser. This application is expected to help the Cempaka Garut Medika Clinic for managing HR data.